Hungarian Monitoring, 6 June 1990 . [Magyar rádiófigyelő], 1990. június 6 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Ethnic conflicts in Kyrgyzstan - Mark Palmer about supporting East European economies - Warsaw Pact meeting Domestic Affairs: - Árpád Göncz takes part at the Warsaw Pact meeting in Moscow - József Antall may meet Gorbachev and Ryzhkov - József Antall and Harri Holkeri about the need to dissolve the Warsaw Pact - Rita Süssmuth's schedule in Hungary - UNESCO head arrives in Budapest - Attempts against László Tőkés's brothers Economy: - Hungary may receive IMF loan Külpolitika: - Etnikai konfliktus Kirgizisztánban - Mark Palmer Kelet-Európa gazdasági segítségéről - Tanácskozik a Varsói Szerződés Belpolitika: - Göncz Árpád Moszkvába utazott a Varsói Szerződés ülésére - Antall József Gorbacsovval és Rizskovval tárgyalhat - Antall József és Harri Holkeri a Varsói Szerződés felszámolásának szükségességéről - Rita Süssmuth magyarországi programja - Az UNESCO főigazgatója Budapestre érkezett - Merényletek Tőkés László fivérei ellen Gazdaság: - Magyarország hitelt kaphat az IMF-től